PENGARUH KOMPENSASI TERHADAP TURNOVER INTENTION PADA MASA COVID-19 PADA KARYAWAN RUMAH MAKAN CIPTA RASA KABUPATEN KETAPANG PROVINSI KALIMANTAN BARAT - SARI, NIRMALA B102117098 (Jurnal Manajemen Update, 2021)
This study aims to determine the effect of compensation on turnover intention with organizational commitment and job satisfaction as moderating variables for employees at Cipta Rasa Restaurant in Ketapang Regency, West Kalimantan Province. This research is a type of comparative causal research. The population in this study were all employees who worked at the Cipta Rasa Restaurant, amounting to 48 people. Based on the sampling technique with non-random sampling obtained a sample of 48 people. Data collection techniques using a questionnaire (questionnaire) using a Likert scale and using interviews. The analysis technique used is descriptive analysis, classical assumption test, partial test (t test), coefficient of determination test (r2), and moderate regression analysis test. The results of this study indicate that Compensation has a negative and significant effect on Turnover Intention, Organizational Commitment (moderating variable) can weaken the relationship between Compensation and Turnover Intention, because there is a negative relationship between Compensation and Turnover Intention, Job Satisfaction (moderating variable) can weaken the relationship between Compensation on Turnover Intention, because there is a negative relationship between Compensation and Turnover Intention.Â Keywords: Compensation, Turnover Intention, Organizational Commitment and Job Satisfaction.Â Daftar PustakaAhmad,Tohardi. 2002. Pemahaman Praktis Manajemen Sumber Daya Manusia. Bandung: BPFE UGMÂ Arsih, R. B., Sumadi, & Susubiyani, A. (2018). Pengaruh Kepuasan Gaji, Kepuasan Kerja Dan Iklim Organisasi Terhadap Komitmen Organisasi Dan Turnover Intention. JSMBI (Jurnal Sains Manajemen Dan Bisnis Indonesia), 8(2), 164-179 e-ISSN:2541-2566 p-ISSN:2088-916X.Â Buchanan, Bruce. (1974). Building Organizational Commitment: The Socialization of Managers in Work Organizations. Administrative Science Quarterly. Vol. 19, Num. 4. pp. 533-546Â Dewi, R. (2017). Pengaruh Iklim Organisasi dan Kepuasan Kerja terhadap Turnover Intentions dan Komitmen Organisasi Sebagai Variabel Intervening Pada Pt. Panca Surya Agrindo (Psa) Kabupaten Rokan Hulu. JOM Fekon, 4(1).Â Dharmawan, Yusa. (2011). Pengaruh Kompensasi dan Lingkungan Kerja Non Fisik Terhadap Disiplin dan Kinerja Karyawan Hotel Nikki Denpasar.Tesis. Universitas Udayana Denpasar. Bali.Â Engko, Cecilia. (2008). â€œPengaruh Kepuasan Kerja terhadap Kinerja Individual dengan Self Esteem dan Self Efficacy sebagai Variabel Intervening.â€ Jurnal Bisnis dan Akuntansi. Vol. 10.No. 1. April 2008. 1-12. Universitas Patimura.Â Ghozali, Imam. (2013). Aplikasi Analisis Multivariate dengan Program IBM SPSS21 Update PLS Regres. Semarang: Diponegoro.Â Gouzali, Imam. (2005). Manajemen Sumber Daya Manusia: Suatu Pendekatan Mikro. Jakarta: Djambaran.Â Gouzali, Imam. (2011). Manajemen Sumber Daya Manusia Jilid 2. Jakarta: Gunung Agung.Â Handoko, H. (2002). Manajemen Sumber Daya Manusia dan Personalia. Yogyakarta: BPFE UGMÂ Hasibuan, Malayu S.P. (2006). Manajemen Sumber Daya Manusia (Edisi Revisi).Jakarta: Bumi Aksara.Â Â Â Â Â Â Â Â Â Â Â Hasibuan, Malayu S.P. (2009). Manajemen Sumber Daya Manusia (Edisi Revisi).Jakarta: Bumi Aksara.Â Husein, Umar. (2014). Metode Penelitian Untuk Skripsi dan Tesis Bisnis. Jakarta : PT.Raja Grafindo Persada.Â Judge, R. dan. (2007). Perilaku Organisasi, terj. Ratna Saraswati. Jakarta:Selemba Empat.Â Kadarisman, M. 2012. Manajemen kompensasi. Jakarta: Rajawali persÂ Koesmono. (2005). â€œPengaruh Budaya Organisasi terhadap Motivasi dan Kepuasan Kerja serta Kinerja Karyawan Pada Sub Sektor Industri Pengolahan Kayu Skala Menengah di Jawa Timur.â€ Jurnal Manajemen & Kewirausahaan. Universitas Petra.Â Lenni, N. (2014). Pengaruh Kompensasi Finansial dan Nonfinansial terhadap Kinerja Karyawan PT. Pertamina EP Bunyu Field kabupaten Bulungan. EJournal Ilmu Administrasi Bisnis, 2(4).Â Lu Lu Allan Cheng Chieh Lu Dogan Gursoy Nathan Robert Neale , 2016,"Work engagement, job satisfaction, and turnover intentions", International Journal of Contemporary Hospitality Management, Vol. 28 Iss 4 pp. 737 Â± 761Â Luthans, Fred. 2006. Perilaku Organisasi, (Alih Bahasa V.A Yuwono, dkk), Edisi Bahasa Indonesia, Yogyakarta: ANDIÂ Mangkunegara, Anwar Prabu. (2005). Evaluasi Kinerja Sumber Daya Manusia.Bandung: Refika Aditama.Â Mangkunegara, Anwar Prabu. (2011). Evaluasi Kinerja Sumber Daya Manusia.Bandung: Refika Aditama.Â Mathis, Jackson. (2004). â€œManajemen Sumber Daya Manusiaâ€. Jakarta: Salemba Empat.Â Mawardi. (2016). Analisis Pengaruh Komitmen Organisasi dan Kepuasan Kerja terhadap Turnover Intention Karyawan Dealer Honda CV Semoga Jaya Cabang Tenggarong. JEMI, 16(2).Â Mowday, R. T., R. M. Steers and I. W. Porter. (1983).â€œThe Measurement of Organizational Commitmentâ€. Journal of Applied Psychology. Vol.84, p.408-414.Â Nawawi, Handari. (2005). Manajemen Sumber Daya Manusia untuk Bisnis YangKompetitif. Yogyakarta : UGMÂ Saputra, M., & Rahardjo, W. (2017). Pengaruh Iklim Organisasi, Kepuasan Kerja, Keterlibatan Kerja Terhadap Komitmen Organisasi Pada Karyawan PT. X. Jurnal Psikologi, 10(1).Â Setyaningrum, W., & Mukzam, M. D. (2018). Pengaruh Kompensasi Finansial dan Kompensasi Non Finansial terhadap Kepuasan Kerja dan Turnover Intention (Studi pada Karyawan PT. PLN (Persero) Kantor Area Bojonegoro). Jurnal Administrasi Bisnis (JAB), 59(1).Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Sugiyono (2012), Metode Penelitian Kuantitatif, Kualitatif Dan R&D, Bandung: Alfabeta.Â Sugiyono. (2015). Metode Penelitian Kombinasi (Mix Methods). Bandung: Alfabeta.Â Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Â Sugiyono. (2018). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Â Sugiyono. (2019). Metode Penelitian Kuantitatif. Bandung: Alfabeta.Â Susetyo, A. (2016). Pengaruh Job Satisfaction dan Pay Satisfaction terhadap Turnover Intention Karyawan dengan Komitmen Organisasional sebagai Variabel Intervening. Jurnal Fokus Bisnis, 15(2).Â Sutrisno, Edy. (2010). Manajemen Sumber Daya Manusia.Jakarta: Kencana Prenada Media Group.Â Tantowi, A. (2016). Pengaruh Kompensasi Finansial dan Non Finansial terhadap Kepuasan Kerja serta Dampaknya terhadap Turnover Intention pada Pelaut Di PT Maritim Barito Perkasa Banjarmasin. Jurnal Wawasan Manajemen, 4(1).Â Wibowo (2011). Manajemen Kinerja. Jakarta: PT. Raja Grafindo Persada